The Dynamics of International Tourism and Economic Growth Convergence in ASEAN+3 - SARA, I Made; DHARMANEGARA, Ida Bagus Agung; KORRI, I Nyoman Sugawa (Journal of Environmental Management and Tourism, 2018)
This study aims to analyze the impact of the tourism sector on economic growth and to identify the convergence of economic growth both in absolute and conditional of ASEAN + 3 countries. The analytical method used is Arellano-Bond Generalized Method of Moment (AB-GMM) with the period of 2003-2015 for 13 ASEAN countries: Brunei Darussalam, Cambodia, Indonesia, Lao PDR, Malaysia, Myanmar, Philippines, Singapore, Thailand and Vietnam plus China, Republic of Korea and Japan. The variables used are Gross Domestic Product (GDP) and International Tourist Arrival. The results show that conditional convergence beta by entering tourism indicator has the speed of convergence process in economic growth compared to without entering the tourism indicator. However, the half-life that needed is long enough to achieve steady-state conditions, and it is important to get the attention of policymakers and relevant stakeholders in accelerating the achievement of growth targets through tourism.